Comparing the results of DAADD and ABC of children included in Autism Spectrum Disorders - Barbosa, Milene Rossi Pereira; Fernandes, Fernanda Dreux Miranda (CoDAS (São Paulo), 2014)
PURPOSE: To verify if there are characteristic behaviors of the different diagnosis included in the autism spectrum according to the Differential Assessment of Autism and Other Developmental Disorders (DAADD) and to the Autism Behavior Checklist (ABC). METHOD: Participants were 45 individuals and their respective speech-language therapists. All therapists are graduate students working with the children for at least 1 year. This time was considered sufficient to the therapists to have the information required by the DAADD questionnaire. It is comprised by 3 protocols specifically designed to children with 2 to 4 years, 4 to 6 years and 6 to 8 years, the same criteria used to separate the research groups, G1, G2 and G3, respectively. Data referring to the ABC were retrieved from the subject's files at the Laboratório de Investigação Fonoaudiológica nos Distúrbios do Espectro do Autismo (Research Laboratory on Language Disorders in the Autism Spectrum) of the School of Medicine, Universidade de São Paulo, where it is routinely applied during the annual assessment. RESULTS: Answers to the different areas of DAADD are similar to the different areas of ABC. These data show data the diagnosis by DAADD is easier in older children. Although there is no significant difference, the large occurrence of Rett's syndrome diagnosis according to the DAADD was associated to higher risk for autism according to the ABC in G1. With increasing age this tendency decreases and either in G2 and G3 Autism is the most frequent diagnosis. CONCLUSION: Although the results of both questionnaires tend to agree more with increasing age, the DAADD is more sensitive in the different ages while the ABC if more specific only to older children. OBJETIVO: Verificar a existência de comportamentos característicos de diferentes quadros incluídos nos Distúrbios do Espectro do Autismo identificados segundo o Differential Assessment of Autism and Other Developmental Disorders (DAADD) e a Autism Behavior Checklist (ABC). MÉTODO: Participaram desta pesquisa 45 indivíduos autistas e suas respectivas terapeutas. Todas as terapeutas são fonoaudiólogas pós-graduandas e atendiam os sujeitos há pelo menos um ano, tempo considerado suficiente para fornecer as informações solicitadas pelo DAADD. Ele é composto por três protocolos especificamente dirigidos a crianças entre dois e quatro anos de idade, quatro e seis anos, e seis e oito anos, o mesmo critério usado para dividir os grupos da pesquisa em G1, G2 e G3, respectivamente. Os dados referentes à ABC foram retirados dos protocolos dos sujeitos, registrados no acervo do Laboratório de Investigação Fonoaudiológica nos Distúrbios do Espectro do Autismo da Faculdade de Medicina da Universidade de São Paulo, uma vez que ele é regularmente aplicado a todos os pacientes durante o processo de avaliação anual. RESULTADOS: As respostas do DAADD, por área, se aproximam das respostas do ABC, também por área. Os dados evidenciam que, conforme a idade aumenta, é mais fácil identificar o diagnóstico pelo DAADD. Apesar de não haver diferença estatisticamente significativa, a grande ocorrência do diagnóstico de SR obtida no DAADD associou-se à alta probabilidade no ABC para o G1. Conforme aumenta a idade, essa prevalência diminui, sendo o autismo mais prevalente no item alta probabilidade tanto para o G2 quanto para o G3. CONCLUSÃO: Apesar de os protocolos serem mais concordantes conforme aumentam as idades, por faixa etária, o DAADD se mostra mais sensível, enquanto o ABC é mais específico apenas para as crianças mais velhas.